ONTOLOGICAL DIMENSION OF UNDERSTANDING IN GADAMER’S HERMENEUTIC - Anselmus Chartino Ade (Muse: Jurnal of Art, 2024)
The focus point of hermeneutic philosophy is “the art of understanding”. Hermeneutic philosophers pay special attention to the interpretation and application of texts. Hans George Gadamer, as one of the figures in hermeneutic philosophy, emphasized that “understanding” has a circular structure. In order for people to understand, there must be pre-understanding. “Understanding” is impossible without language because it is a fundamental human attitude, which also relate with past texts. “Understanding” essentially has ontological relevance. The ontological dimension shows an existential relationship between words and objects. Looking for a word is actually nothing more than looking for a word that seems to be attached to an object. This word is a statement of the complete identity of reality. Words or language come from reality. The formulation “the conversation that we ourselve are” sounds similar with Rene Descartes' “cogito ergo sum”. If Cortesio’s res cogitans is thought, then for Gadamer it is language and conversation. The reason of Gadamer is actually very classic, that no thought can exist outside of words and language